Generational Accounting in Europe - Raffelhüschen, Bernd (American Economic Review, 1999)
In most member states of the European Union (EU), issues concerning sound and sustainable finances are high on the political agenda. This paper briefly reports the findings of 12 country studies that investigate the impact of the demographic transition on the intergenerational stance of current fiscal policy within EU, using the device of generational accounting as first developed by Alan J Auerbach et al. (1991).